Yield and nutraceutical quality of tomato fruits in organic substrates - Salas Pérez, Lilia; García Hernández, José Luis; Márquez Hernández, Candido; Fortis Hernández, Manuel; Estrada Arellano, Josue Raymundo; Esparza Rivera, Juan Ramón; Preciado Rangel, Pablo (Ecosistemas y Recursos Agropecuarios, 2016)
The objective of this study was to determine the proportion of sand, solarized manure, vermicompost and soil capable of increasing tomato fruit yield and lycopene content. The treatments were: T1: 80 % Sand- 20 % Vermicompost (SV), T2: 80 % Sand- 20 % Solarized manure (SSM1), T3: 80 % Sand - 20 % Pelite ?Steiner solution (SPSS), T4: 80 % Sand- 5 % Soil - 15 % Vermicompost (SSoV), T5: 85 % Sand - 15 % Solarized manure (SSM2) and T6: 80 % Sand - 5 % Soil - 15 % Solarized manure (SSoSM). The organic substrates T5, T4, T1 and the control (T3) obtained larger fruits and yields. The lycopene content in tomato fruits grown in the organic substrates was 26 % higher than that obtained in the control treatment. Organic fertilizers improve the nutraceutical quality of tomato fruits, without signi cantly degrading yield.
Keywords: organic fertilizers; lycopene; protected agricultura